Study on the mechanism of andrographolide activation - Cai, Qihan; Zhang, Weina; Sun, Yanan; Xu, Lu; Wang, Mengmeng; Wang, Xinliang; Wang, Siming; Ni, Zhiyu (Frontiers in Neuroscience, 2022)
Andrographolide is a natural antibiotic that has the ability to dispel heat, detoxify, reduce inflammation, and relieve pain. Recent research has shown that it can exert anti-inflammatory effects via multiple pathways and multiple targets (mediated by NF-κB, JAK/STAT, T cell receptor, and other signaling pathways). It can inhibit human lung cancer cells, colon cancer cells, osteosarcoma cells, and other tumor cells, as well as reduce bacterial virulence and inhibit virus-induced cell apoptosis. It can also regulate inflammatory mediator expression to protect the nervous system and effectively prevent mental illness. Additionally, andrographolide regulates the immune system, treats cardiovascular and cerebral vascular diseases, protects the liver, and the gallbladder. It is clear that andrographolide has a huge range of potential applications. The mechanism of andrographolide's anti-inflammatory, antibacterial, antiviral, and nervous system defense in recent years have been reviewed in this article.